Biochemical and microbiological changes of pink perch (Nemipterus japonicus) surimi stored at different temperatures - Singh, R K; Balange, A K (Indian Journal of Fisheries, 2011)
Investigations on factors responsible for spoilage of frozen surimi of pinkperch (Nemipterus japonicus) stored at ambient (25 to 280 C), refrigerator(6.5 to 7.50 C) and at deep freezer temperatures (-8 to -100 C), interms of organoleptic quality, bacterial load and biochemical indices indicatedthat at ambient temperature, frozen surimi can be preserved forabout 8 hrs, while at refrigerator temperature up to 5 days and at deepfreezer temperature up to 60 days. Bacterial count, trimethylamine andtotal volatile nitrogen values increased with storage time while, organolepticscore decreased. Nutrient contents and gel strength of surimidecreased while, moisture and whiteness increased with storage period.